1993
DOI: 10.1063/1.464259
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence excitation spectra of jet-cooled HgBr radicals

Abstract: Fluorescence excitation spectra of HgBr radicals produced and rotationally cooled in a corona-excited supersonic jet discharge are presented. Both the C 2Π1/2←X 2Σ+ transition near 287.6 nm and the B 2Σ+←X 2Σ+ transition near 350.0 nm were studied. Transitions from X 2Σ+ (vX=0–2) probe very high vibrational levels in the B 2Σ+ ion-pair state (vB=34–90). Analysis of the vibrationally and isotopically resolved spectral features has yielded an unambiguous vibrational numbering for the B←X spectrum and precise B-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…There is only limited experimental information on the structure and stability of HgO and HgBr. , Fortunately, the structures and stabilities of the Hg(II) dihalides are better known, from both experiment and calculation . There have been a number of calculations of the properties of Hg compounds within the theoretical inorganic literature. , In a recent, very accurate study 15e the gas-phase species HgO was found to be stable with respect to Hg 0 and ground state O by only 4 kcal/mol, compared to an experimental value of 53 ± 10 kcal/mol 12c…”
Section: Introductionmentioning
confidence: 99%
“…There is only limited experimental information on the structure and stability of HgO and HgBr. , Fortunately, the structures and stabilities of the Hg(II) dihalides are better known, from both experiment and calculation . There have been a number of calculations of the properties of Hg compounds within the theoretical inorganic literature. , In a recent, very accurate study 15e the gas-phase species HgO was found to be stable with respect to Hg 0 and ground state O by only 4 kcal/mol, compared to an experimental value of 53 ± 10 kcal/mol 12c…”
Section: Introductionmentioning
confidence: 99%